PENGARUH MEDIA GAME EDUKASI BERBASIS QUIZIZZ PAPER MODE TERHADAP MINAT BELAJAR ILMU PENGETAHUAN ALAM DAN SOSIAL PESERTA DIDIK KELAS IV SEKOLAH DASAR NEGERI 3 DUWET KLATEN - Destika Ade Kurniawati; Dwi Anggraeni Siwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine whether there is an influence of the use of Educational Game media based on Quizizz Paper Mode on the interest in learning Natural and Social Sciences of grade IV students of Elementary School 3 Duwet Klaten. This study uses a quantitative approach with an experimental method which means comparing the results of a treatment with no treatment, and implementing the Non Equivalent Control Group Design design. As a result, this study used 2 classes as research samples, namely the experimental class from Elementary School 3 Duwet with 16 students and the control class from Elementary School 1 Duwet with 17 students. The data collection technique used in this study was a questionnaire and documentation with the research instrument being a learning interest questionnaire with the help of SPSS 22 which was carried out in two stages, namely before treatment (Pretest) and after treatment (Posttest). The data analysis technique in this study was in the form of a normality test, a homogeneity test, and a hypothesis test using a t-test with the Independent sample test type. Based on the results of the prerequisite analysis test, it shows that the data is normally distributed and homogeneous while in the t-test the results obtained are sig (2-tailed) = 0.000 ˂ 0.05. Thus, it is concluded that there is an influence of the use of Educational Game media Based on Quizizz Paper Mode on the interest in learning Natural and Social Sciences of grade IV students of State Elementary School 3 Duwet Klaten.